Intimate citizenship and compensatory masculinities - Fataneh Farahani; Amani Al-Serhan; Suruchi Thapar-Björkert (Kulturella Perspektiv, 2024)
This study explores the complex conditions of cross-border marriages between Syrian refugee women and Jordanian men in Mafraq, Jordan, within the context of South-South migration. Through qualitative interviews in Mughayyir, Raba', and Zaatari, the research examines specific gendered and raced relations shaped by discourses and practices of femininity and masculinity. Racialized gendered dynamics portray the strategic mobilization of non-hegemonic and 'compensatory masculinities' among Jordanian men in response to Syrian women's perceived vulnerability. Drawing on Ken Plummer's 'intimate citizenship,' the study scrutinizes marriage decision-making entangled with political discourses, revealing the imbrication of personal lives with globalized politics, embedded within the gendered patriarchal demands of the hosting society. In contrast to studies on North-South cross-border marriages, this research focuses on the South, shedding light on non-migrant husbands' experiences and their compensatory strategies. The 'intimate citizenship' framework illuminates challenges surrounding desirable and undesirable unions within displaced Syrian women and Jordanian men, unveiling the politicization and stigma associated with cross-border marriages. By addressing societal judgments and introducing 'heterosexual capital' and 'compensatory masculinity,' the research enriches our understanding of South-South migration complexities, prompting a reevaluation of existing frameworks and fostering a more nuanced discussion.